Ciclo de Vida a partir das Características Institucionais das Cooperativas Agroindustriais no estado de Mato Grosso do Sul. - ALTAIR GONÇALVES (2024)
This study investigated the phases of the organizational life cycle based on institutional characteristics, in the agro-industrial cooperative sector. This model of collective enterprise is expanding in Mato Grosso do Sul - MS, mainly in the agricultural sector, demonstrating the influence of the state's economic matrix, justifying the research and demonstrating the importance for academic purposes and support in the discussion of possible public incentive policies to this sector. The general objective was to analyze the life cycle phases of cooperatives with agro-industrial activities in MS in 2023, through the characterization of these cooperatives based in this state, the identification of institutionalization characteristics and identification of the phases of the organizational life cycle. The research approach was through the qualitative method and descriptive analysis of the objectives, using databases from secondary sources from the Federal Revenue of Brazil - RFB, the Organization of Cooperatives of Brazil - OCB/MS and documentary research via consultation of events registered in the State Commercial Board - JUCEMS. In the first stage, 200 (two hundred) cooperatives were characterized, located in 76 municipalities and in all economic regions of the state. Of these, 97 (ninety-seven), 48.50% were characterized as being in the agricultural sector, 24 (twenty-four) with irregularities in the OCB/MS registration were removed, leaving 73 (seventy-three). Afterwards, it was characterized by industrial activities and the sample was delimited into 21 (twenty-one) cooperatives. In the second stage, through documentary and electronic research of the events registered in the sample's JUCEMS, the characteristics of institutionalization were identified: registration in the OCB/MS; active status at JUCEMS; registration of Assembly Acts of Constitution and Accountability; numbers of cooperative members; membership growth; participation of cooperative members in Ordinary General Meetings - AGO; and making results available for deliberation. In the third stage, the phases of the organizational life cycle of agro-industrial cooperatives in MS were identified, through the relationship with the institutionalization characteristics identified. In this association, it was identified that of the 21 (twenty-one) cooperatives in the sample, 2 (two) are in the Initial stages, 13 (thirteen) in the Reflection phase, 3 (three) in the Glory, Growth and Heterogeneity phase and 3 (three) in the Selection phase [exit]. This finding assumes that most cooperatives need to review their initiatives, strategies and strengthen accountability to members to reduce information asymmetry through the disclosure of financial statements. It is concluded that the objectives proposed in the study were met and contribute to the understanding of this sector and demonstrate research gaps that can be explored by researchers and academics in Accounting Sciences. Keywords: Organizational Life Cycle; Institutionalization; Agroindustrial Cooperative; Agricultural Sector.